THE EFFECTS OF STUDENT’S SELF CONFIDENCE AND VOCABULARY MASTERY TOWARDS SPEAKING SKILL. - Teddy Setiawan; Muhammad Sulhan (INFERENCE: Journal of English Language Teaching, 2021)
The objectives of this research is to know the Effects of Self-confidence and Vocabulary Mastery towards Students’ Speaking Skill – Survey at State Vocational High Schools, Tangerang City, Banten. The research populations were 600 students and the samples were 60 students taken from eleventh grade SMKN 7 and SMKN 9 vocational high schools at second semester of 2019/2020 academic year in Tangerang city. The instruments of the research were composed of 25 items of vocabulary test questions and 40 items questionnaire of students’ self-confidence. This research was designed and calculated using quantitative calculation. The major findings of the research indicates that the effects of self-confidence and vocabulary mastery towards the students’ speaking skill of eleventh grade Tangerang City Vocational High School is of high level category. The results of the research are as follow:1)There are any significant effects of self-confidence and vocabulary mastery jointly towards students’ speaking skill at the State Vocational High Schools in Tangerang City, Banten. It is proved by the value of Sig is 0.000<0.05 and the value of Ftest is 45.105. 2) There is a significant effect of self-confidence towards students’ speaking skill. It is proved by the value of Sig 0.042<0.05 and ttest of 2.075. 3) There is no significant effect of vocabulary mastery towards students’ speaking skill at the State Vocational High Schools in Tangerang City, Banten. It is proved by the value of Sig is 0.138>0.05 and ttest 1.502. Based on the research findings it can be recommended that speaking skill requires high level of self-confidence and adequate vocabulary mastery. Speaking skill is not only influenced by vast amount of vocabulary mastery but other influential factors at the state vocational high schools in Tangerang city such as high level of self-confidence.Keywords: Self-confident, Speaking Skill and Vocabulary Mastery.